A queue state driven analysis of IEEE 802.11 DCF for ad hoc networks under non-saturation conditions. (2016) - Abbas, Ash Mohammad; Soufy, Khaled Abdullah Mohammed Al
In this paper, we present a queue state driven analysis of IEEE 802.11 DCF for an ad hoc network under non-saturation conditions. In our analysis, we focus on the average end-to-end delay, throughput, and the loss probability for a network consisting of single hop as well as multiple hops along a path from a given source to a destination. We study the effect of collision probability, probability of packet transmissions, the transmission range/carrier sense range, and the number of buffers in the queue. To validate the analysis, we carried out simulations and observed that the simulation results are in accordance with the analytical results.